Hubungan Miopia dengan Konsentrasi Belajar pada Siswa Siswi MAN 1 Medan - Rizky Kurniawan Risaf; Taufik Akbar Faried Lubis; Zaldi Z; Heppy Jelita Sari Batubara (UMSU, 2025)
Myopia is a refractive disorder in which the image is focused in front of the retina due to improper eye accommodation.19 Myopia can result in difficulty seeing distant objects, posing significant challenges in the classroom, particularly when students need to clearly view the blackboard or other learning materials. This visual impairment has the potential to reduce academic performance, as students may struggle to follow lessons effectively, thereby disrupting their ability to concentrate on learning.12 Learning concentration itself is the process of directing one’s attention and thoughts toward learning activities while disregarding irrelevant information in order to focus on specific subject material.25 Methods: This type of research is descriptive analytic research with a cross sectional design. In this study using a sample of 333 people. The data test in this study used univariate test and bivariate test of Chi-Square test. Results: Out of the total of 333 respondents, the largest age group was 16 years old, comprising 122 individuals (36.6%), with the majority being male, totaling 198 respondents (40.5%). The majority of respondents were found to have myopia, with 213 individuals (64%), while 120 respondents (36%) did not experience myopia. A total of 119 respondents (35.7%) reported using eyeglasses, while 214 respondents (64.3%) did not. The level of students’ learning concentration was categorized as high for 120 respondents (36%), moderate for 110 respondents (33%), and low for 103 respondents (30.9%). The Chi-Square statistical analysis revealed a significant relationship between myopia and learning concentration, with a p-value of 0.000 (0.05). Conclusion: There is a significant relationship between the relationship between myopia and learning concentration of students of MAN 1 Medan.